Evaluation of the National Comprehensive Cancer Network and European Society for Medical Oncology Nasopharyngeal Carcinoma Surveillance Guidelines - Zhou, Guan-Qun; Lv, Jia-Wei; Tang, Ling-long; Mao, Yan-Ping; Guo, Rui; Ma, Jun; Sun, Ying (Frontiers in Oncology, 2020)
Purpose: The National Comprehensive Cancer Network (NCCN) and European Society for Medical Oncology (ESMO) provide surveillance guidelines for nasopharyngeal carcinoma (NPC). We evaluated the ability of these guidelines to capture disease recurrence. Materials and methods: All 749 NPC patients were stratified for analysis by T and N stage. Guidelines were assessed by calculating the percentage of recurrences detected when following the 2018 NCCN, 2015 NCCN and 2012 ESMO recommendations, and associated surveillance costs were compared. Results: At a median follow-up of 100.8 months, 168 patients (22.4%) had experienced recurrence. Nineteen recurrences (11.3%) were detected using the 2018 NCCN, 53 (31.5%) using the 2015 NCCN and 46 (27.4%) using the ESMO guidelines. To capture 95% recurrences, surveillance would be required for 85.57 months for T1/2, 67.45 months for T3/4, 83.57 months for N0/1 and 55.80 months for N2/3 disease. In T1/2 disease, Medicare surveillance costs per patient were US$1642.66 using 2018 NCCN or ESMO and US$2179.81 using 2015 NCCN. Costs per recurrence detected were US$42,578.64, 62,088.70 and 73,329.76 using 2018 NCCN, 2015 NCCN and ESMO respectively. Conclusions: If strictly followed, the NCCN and ESMO guidelines will miss more than two-thirds recurrences. Improved surveillance algorithms to balance patient benefit against costs are needed.